Examining the Mediating Role of Altruism in the Relationship between Empathic Tendencies, the Nature Relatedness, and Environmental Consciousness - Nudar Yurtsever; Duriye Esra Angın (Center for Educational Policy Studies Journal)
A study was conducted using a correlational screening model to determine the mediating effect of altruism in the relationship between empathic tendencies, the nature relatedness and environmental consciousness. The participants of the study, selected via random cluster sampling design, are composed of 305 pre-school teachers working in pre-schools and kindergartens in a city located in Turkey’s Aegean region. The ‘Empathic Tendency Scale’, ‘Altruism Scale’, ‘Nature Relatedness Scale’, and ‘Environmental Consciousness Scale’ were used as data collection tools. The analyses of the sub-purposes were carried out using the PROCESS macro (Model 4) developed by Andrew Hayes using the SPSS infrastructure. When the study results were examined, the indirect effects of the empathic tendency on nature relatedness and environmental consciousness were found to be significant. Thus, altruism was the mediator for the relationship between the empathic tendency and nature relatedness (β=.13, 95% BCA CI [.08; .19]) and for the relationship between emphatic tendency and environmental consciousness (β=.36, %95 BCA CI [.18; .57]).